2004
DOI: 10.1176/ajp.161.10.1798
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of COMT Val108/158 Met Genotype and Olanzapine Treatment on Prefrontal Cortical Function in Patients With Schizophrenia

Abstract: These results suggest that a genetically determined variation in prefrontal dopamine catabolism impacts the therapeutic profile of olanzapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
61
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(71 citation statements)
references
References 50 publications
9
61
1
Order By: Relevance
“…However, this difference in the response to the neuroleptic treatment was not identified in the remaining PANSS subscales, which could be explained by the sample size (20 and 30 patients, respectively; 8 weeks of treatment). Our results, using the GAF and the PANSS scales, and a longer period of treatment (6 months), although showing a small effect, are in good agreement with those obtained by Bertolino et al 36 and Weickert et al 37 In our sample, the Val/Val genotype was associated with a higher severity of psychotic symptoms measured by the PANSS scale ( Figure 1) and a smaller enhancement of the global functioning after period of treatment measured by the GAF scale than Met/Met and Val/Met patients ( Figure 2).…”
Section: Panss-t Panss-p Panss-n Panss-g Responderssupporting
confidence: 92%
See 3 more Smart Citations
“…However, this difference in the response to the neuroleptic treatment was not identified in the remaining PANSS subscales, which could be explained by the sample size (20 and 30 patients, respectively; 8 weeks of treatment). Our results, using the GAF and the PANSS scales, and a longer period of treatment (6 months), although showing a small effect, are in good agreement with those obtained by Bertolino et al 36 and Weickert et al 37 In our sample, the Val/Val genotype was associated with a higher severity of psychotic symptoms measured by the PANSS scale ( Figure 1) and a smaller enhancement of the global functioning after period of treatment measured by the GAF scale than Met/Met and Val/Met patients ( Figure 2).…”
Section: Panss-t Panss-p Panss-n Panss-g Responderssupporting
confidence: 92%
“…Thus, the effect of Val 158 Met in the response to treatment seems to be especially clear in terms of negative symptoms. These results, together with those obtained by Bertolino et al 36 and Weickert et al, 37 suggest that the advantage conferred by the Met allele in the response to the neuroleptic treatment is evident shortly after the administration of the neuroleptic drugs, and it seems to be still detectable after 6 months of treatment. It would be interesting to investigate this effect in larger series with longer periods of treatment to clarify the magnitude of this effect in the long-term prognosis.…”
Section: Panss-t Panss-p Panss-n Panss-g Responderssupporting
confidence: 63%
See 2 more Smart Citations
“…Although some reports are questioning the size of the effect and specificity of the cognitive effects of second-generation antipsychotics (Goldberg et al, 2007;Keefe et al, 2007), some evidence shows that this treatment is associated with improvement of some of the cognitive deficits of schizophrenia including WM (Bertolino et al, 2004;Purdon et al, 2000). Furthermore, second-generation antipsychotic treatment appears to modulate brain physiology underlying WM function with reduced activation of dorsolateral prefrontal cortex (DLPFC) and parietal cortex for better levels of performance, suggesting increased neural efficiency (Bertolino et al, 2004). Moreover, other studies have indicated that systemic administration of levodopa and apomorphine in healthy humans or in patients with Parkinson's disease can modify the activity of the DMN (Argyelan et al, 2008;Nagano-Saito et al, 2009) further suggesting the potential relationship between dopamine signaling and DMN modulation.…”
Section: Introductionmentioning
confidence: 99%